PENGARUH MODE GETAR DAN ASPEK RASIO TERHADAP DISTRIBUSI TEGANGAN PADA FIBER METAL LAMINATES - Khairul Anam; Anindito Purnowidodo; Tamara F. Utama; Djarot B. Darmadi; Ari Wahjudi; Agung Sugeng Widodo (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
Fiber metal laminates (FMLs) are widely used in various fields such as automotive and aerospace due to their high stiffness and strength-to-weight ratios. Moreover, they also have high fatigue resistance. In some applications such as aircraft structures, it is crucial to do dynamic analysis of the FMLs structure. FMLs compose of aluminium and fiberglass reinforced polymers (FRPs) are used in this study. The aim of this study is to investigate the effect of shape mode and aspect ratio on the stress distribution of FML by using finite element analysis software. Ten initial mode shapes and the aspect ratio of 1:1.5, 1:2, and 1:2.5 are used as the environmental conditions of the FMLs. The results indicate that the mode shape will change the stress distribution and the maximum stress position. Besides, the results have shown that a wider FMLs plate will increase the maximum stress and deformation. The maximum to minimum stress distribution occurs on the outer aluminium surface, the inner aluminium surface, and the FRPs surface, respectively.